Ratooning as a management strategy for lodged or drought‐damaged rice crops - Torres, Rolando O.; Natividad, Mignon A.; Quintana, Marinell R.; Henry, Amelia (Wiley, 2020)
Rice (Oryza sativa L.) plants have the ability to develop ratoon tillers if the terminal growing point is lost, such as when the panicle has been aborted, matured, or harvested. We examined postharvest and midseason ratooning as management strategies for damaged rice crops, both in irrigated and rainfed conditions. Genotypic variation was observed in terms of postharvest ratoon tillering, midseason ratoon crop growth after lodging, and midseason ratoon crop growth after drought stress. The genotypic variation in postharvest ratoon tillering was related to stem carbohydrate levels at the time of main crop harvest and was affected by soil moisture levels at the time of main crop harvest. Drought‐tolerant varieties did not consistently show improved ratoon crop growth. After lodging, cutting stems at a height of 30 cm produced the highest numbers of ratoon tillers, and the contribution of the ratoon crop to the total harvestable grain yield was highest when the ratoon crop was initiated at earlier growth stages. The highest ratoon grain yields recovered from lodged crops ranged up to 3.58 t ha−1. Total grain yield after drought was improved by trimming the leaves and panicles only in certain conditions and did not appear to be correlated with stem carbohydrate levels. These results suggest that management strategies may be recommended to farmers that exploit the ratooning ability of rice for improved recovery after midseason crop damage.